Design, Production and Evaluation of Digital Educational Content Based on DDD-E Model: Depression Treatment in Traditional Persian Medicine - Zohreh Khoshgoftar; Samaneh Tahmasebi Ghorabi; Arian Karimi Rouzbahani; Manijeh Kamran; Ghazaleh Heydarirad; Zahra Goudarzi (Tehran University of Medical Sciences, 2024)
Multimedia conveys educational concepts and materials in an easier, wider, and more attractive way, along with text, sound, image, and video, to overcome the limitations caused by educational methods. The aim of the current research is to produce and evaluate digital multimedia based on the decide, design, develop, and-evaluate (DDD-E) model in the field of teaching depression treatment in traditional Persian medicine. The study was quantitative, and the professors and doctoral students of the two fields of medical education and traditional Persian medicine were the subjects of the present study. In this research, the DDD-E model was used to produce a training package for the treatment of depression in traditional Persian medicine. This study was conducted in four phases: decision-making, planning, development, and evaluation. The final evaluation was done in two stages. First, it was evaluated by preparing a checklist of educational multimedia production stages based on the original DDD-E model, and in the second stage, a QAMLM questionnaire was used to evaluate the final product. The results of the evaluation showed that, according to the evaluators, quality components were generally observed in multimedia production. There was a complete consensus among the experts regarding the quality of content matching the goal and attention to learning results (Kappa coefficient = 1). Regarding the quality of media selection components (Kappa coefficient = 0.383), Paying attention to cultural and social factors (Kappa coefficient = 0.395) There was the least consensus. The overall score of the multimedia produced was equal to 58.4, according to experts. The multimedia was produced in terms of content, education, and technology to provide training to general practitioners in order to improve practical knowledge and use the recommendations of traditional Persian medicine to adjust the treatment patterns of patients with depression.